2005
DOI: 10.1128/aac.49.8.3572-3574.2005
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Synergy Testing of Anidulafungin with Itraconazole, Voriconazole, and Amphotericin B against Aspergillus spp. and Fusarium spp

Abstract: The in vitro interactions of anidulafungin with itraconazole, voriconazole, and amphotericin B were evaluated by using the checkerboard method. For Aspergillus spp., anidulafungin with amphotericin B showed indifference for 16/26 isolates, while anidulafungin with either azole showed a synergy trend for 18/26 isolates. All drug combinations showed indifference for 7/7 Fusarium sp. isolates.Invasive fungal infections due to molds are becoming more prevalent in immunocompromised patients (21). Among the invasive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
40
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(45 citation statements)
references
References 19 publications
3
40
0
2
Order By: Relevance
“…Consistent with the findings of Azor et al (6) and others (5,15,26,41,44,48,49), the 10 antifungals tested in the present study showed very poor in vitro activities against 19 phylogenetically diverse members of the FSSC. The most significant finding from the susceptibility testing is that the polyene AMB showed the highest activity against members of the FSSC (Table 4); however, the MICs for AMB were highly varied.…”
Section: Phylogenetic Diversity Of Fssc Clinical Isolatessupporting
confidence: 81%
See 1 more Smart Citation
“…Consistent with the findings of Azor et al (6) and others (5,15,26,41,44,48,49), the 10 antifungals tested in the present study showed very poor in vitro activities against 19 phylogenetically diverse members of the FSSC. The most significant finding from the susceptibility testing is that the polyene AMB showed the highest activity against members of the FSSC (Table 4); however, the MICs for AMB were highly varied.…”
Section: Phylogenetic Diversity Of Fssc Clinical Isolatessupporting
confidence: 81%
“…Even though the triazole VORI exhibited poor in vitro activity against phylogenetically diverse members of the FSSC in the present and prior studies (6,15), VORI has been used successfully to treat some patients where AMB therapy failed to be efficacious (42). Because FSSC isolates have been reported to exhibit greater resistance to antifungals than other fusaria in some studies (15,41,49) but not others (26,44), future in vitro susceptibility tests need to evaluate these findings by use of sufficient numbers of isolates that have been characterized phylogenetically via MLST (37) so that statistically significant conclusions can be drawn. In addition, studies are needed to evaluate whether and to what extent species-and strain-specific differences in antifungal susceptibility exist within Fusarium (26).…”
Section: Phylogenetic Diversity Of Fssc Clinical Isolatesmentioning
confidence: 96%
“…Indifference was also reported when VOR was combined with the echinocandin CAS (16). In vitro synergy between VOR and ANI was only demonstrated in studies providing alternative interpretations of MIC endpoints being prominent growth reduction endpoints (32).…”
Section: Discussionmentioning
confidence: 99%
“…In the checkerboard assay, the FICI model has been frequently used to determine the interaction between antifungal drugs (7,9,12,17,21,23). The ⌬E model is a useful method for characterizing drug interactions.…”
mentioning
confidence: 99%